Shaping Nepal’s Development from Belt and Road Initiative Project: Geopolitical Dynamics (Research Nepal Journal of Development Studies, 2025)
Belt and Road Initiative (BRI) project has expanded from China to over 150 countries across Asia, Europe, Africa and Middle East. BRI offers both opportunities and challenges to Nepal situated between emerging economic countries, China and India. This paper thus discusses geopolitical dynamics and regional connectivity as well as developmental opportunities and challenges for Nepal. This study used library based review method. Required information were generated from secondary sources of data. The study used comparative analysis method to focuses on macro-level dynamics, its findings are contextualized within the broader global discourse on infrastructure development and regional geopolitics. The study found that BRI can offers economic transformation, regional connectivity, and infrastructure development in Nepal. The country can becomes regional trade and logistics hub, enhancing cross-border trade in South Asia.  However, its success requires addressing key challenges such as debt distress, governance, and geopolitical complexities. Nepal must adopt transparent financial practices, enhance institutional capacity, and maintain a balanced approach to its geopolitical environment, fostering cooperation with both India and China. Therefore, BRI must address potential debt distress by prioritizing concessional financing and transparent terms, ensuring robust financial oversight, and aligning projects with national priorities to avoid fiscal overburden. Governance and institutional capacity are critical, requiring transparent procurement, anti-corruption measures, and efficient project monitoring to mitigate delays and cost overruns. In doing so, Nepal can navigate the BRI’s geopolitical dynamics effectively while ensuring sustainable and inclusive development. This study contributes to the discourse on regional cooperation and strategic alignment, providing insights into how Nepal can harness the BRI to achieve sustainable development while maintaining its strategic autonomy.